2009
DOI: 10.1016/j.jmb.2009.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Regioselectivity in the Enzymatic Chlorination of Tryptophan

Abstract: The regioselectively controlled introduction of chlorine into organic molecules is an important biological and chemical process. This importance derives from the observation that many pharmaceutically active natural products contain a chlorine atom. Flavin-dependent halogenases are one of the principal enzyme families responsible for regioselective halogenation of natural products. Structural studies of two flavin-dependent tryptophan 7-halogenases (PrnA and RebH) have generated important insights into the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
200
0
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(223 citation statements)
references
References 38 publications
11
200
0
12
Order By: Relevance
“…6 A and B) are superimposable. Although we could not determine a substrate pyrrolyl-S-ACP cocrystal structure for either Bmp2 or Mpy16, the position of the pyrrole binding sites for Bmp2 and Myp16 was inferred by a structural alignment of Bmp2 and Mpy16 with the crystal structures of substrate-bound forms of the flavin-dependent tryptophan-7-chlorinases PrnA (16) and RebH (17). Fittingly, the postulated pyrrole-binding site in Bmp2 and Mpy16 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A and B) are superimposable. Although we could not determine a substrate pyrrolyl-S-ACP cocrystal structure for either Bmp2 or Mpy16, the position of the pyrrole binding sites for Bmp2 and Myp16 was inferred by a structural alignment of Bmp2 and Mpy16 with the crystal structures of substrate-bound forms of the flavin-dependent tryptophan-7-chlorinases PrnA (16) and RebH (17). Fittingly, the postulated pyrrole-binding site in Bmp2 and Mpy16 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the active site of Bmp2-TM exhibited no perturbation of the bound FAD cofactor with respect to WT Bmp2, nor did it lead to any apparent change in halogen binding properties of the enzyme, as demonstrated by conservation of its specificity for bromide. Already, for flavin-dependent tryptophan halogenases, it has been demonstrated that amino acid side chains that constitute the substrate binding site control the regiochemical outcomes for halogen additions (17,24,25 this observation to flavin-dependent halogenases that catalyze halogenation of aromatic substrates acylated to ACPs in demonstrating that side chains of residues lining the putative halogenase active site play a role in controlling substrate access, and potentially in specifying the positions on the pyrrole ring that are accessible to halogenation. Unfortunately, in the case of Mpy16, efforts to alter the putative substrate-binding cavity to resemble that of Bmp2 resulted in insolubility of the mutant Mpy16 enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The first enzyme, PrnA (tryptophan 7-halogenase), incorporates the chlorine into the substrate tryptophan (6). Structural and biochemical analyses of both tryptophan 7 and 5-halogenase (7)(8)(9)(10) have established a novel chemical mechanism of hypohalous acid formation at the flavin cofactor, followed by N-chlorolysine formation (9) and finally regioselective halogenation of tryptophan (controlled by orientation of substrate) (10,11). PrnB converts 7-Cl-tryptophan into monodechloroamino-pyrrolnitrin, although the chirality of the PrnB substrate has remained unclear (4).…”
mentioning
confidence: 99%
“…In contrast, our current study focuses on flavin-dependent halogenases, which employ FAD as a cofactor and use a halide anion and molecular oxygen to produce hypochlorous acid as a halogenating agent. Protein crystallography greatly helped in understanding the structural basis of regioselective formation of the carbon-halogen bond (50)(51)(52)(53). A. mellea halogenase genes encode the signature motif GW(A/V)W(F/L)I.…”
Section: Discussionmentioning
confidence: 99%